Smart Hand washing Machine for Community Service During the COVID-19 Pandemic: A Cost Effective Approach for Robust Hand Hygiene - Davinder Singh Rathee, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Hand hygiene is most important practices to prevent the spreading of COVID-19, and other infection for communicable diseases, corona , trachoma, scabies, pneumonia, cholera and eye infections and dysentery, as per the recommendations by World Health Organization (WHO). Several guidelines are recommended for cleaning hand thoroughly which mainly consist of six steps. Mostly used system in surrounding is foot based/mechanical are not ease of use as well as may not suitable for all kind of people. This work presents designing of smart electrical system/touch less as well as designing of physical structure for robust hand washing system, which may be used at public places like restaurants, bus stands, students area and places of food selling etc. This system based on sensor for detecting the presence object. The inbuilt receiver inside sensor detects the reflected 38Khz IR signal in the presence of obstacle and activates the tap valve and facilitates the water flow.